Reducing Academic Stress with Group Counseling with A Combination of Relaxation Techniques and Reading Al-Qur'an - Tiyas Pratiwinata; Tuanasmah Tohdeng (Pamomong: Journal of Islamic Educational Counseling, 2023)
This study aims to determine the effectiveness of group counseling using the relaxation technique of reading the Qur'an to reduce the stress of academic students. academic stress. This type of research is quantitative research. The method used is quasi-experimental, nonquivalent control group design. Data analysis method using independent sample t test. The sample in this study amounted to 16 people, 8 people for the experimental group and 8 people for the control group. Data collection was carried out using the academic stress scale. Based on the results of the study, the Independent Sample T Test test produced a significance value (probability of error) = 0.004. This means that the statistical test results produce a sig value. 0.004˂ α 0.05, meaning that there is a difference in the acquisition score treated with the relaxation technique of reading Al-Qur'an with those who are not treated. Therefore, the class average value in the experimental group is greater than the control group (30.0010.00). Thus, it can be stated that group guidance with relaxation techniques reading the Qur'an is effective for reducing students' academic stress